Self-help skills for people with autism : a systematic teaching approach - 4 0 16; 1950- Anderson, Stephen R.,;Jablonski, Amy L.,;Thomeer, Marcus L.,;Knapp, Vicki Madaus; 5 (Bethesda, Maryland : Woodbine House, 2007)
A comprehensive guide for children with autism that teaches basic self-help skills including communication and social skills, personal hygiene, and academic skills.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Rehabilitation. -- Autism in children.;Autistic children;Self-help techniques.;Parents of autistic children.;Child rearing.;Autism.;Parents of handicapped children; 20; 2